Espaço absoluto no ensaio kantiano do primeiro fundamento da distinção das regiões no espaço (1768) - Marques, José Luciano Verçosa (Universidade Federal de São Carlos, 2015)
The main objective of this dissertation is to present the kantian text Concerning to the first principle of distinction of regions in space, from 1768, under a perspective that goes over the simple conception from Kant against the relational theory of space. If this aspect is important in 1768, definitely is not the only one. The kantian argument is, in itself, more complex, because, besides proving of the reality of absolute and unique space, it involves more concepts. Firstly, the kantian argument can t be understood without reference to the method utilized by the philosopher in his exposition. Secondly, by the same reason, the kantian argument against Leibniz can t be understood by the merely defense of newtonian absolute space, even though it s quite closely to this notion. In third place, in the position to intend to prove the absolute space s reality, the argument of 1768 Essay has consequences to the manner in which we have to represent the space. Finally, as consequence the 1768 s argument against leibnizianian conception of relational space has consequences to the own way in which Kant interprets the substance s metaphysics of Leibniz. In this way, when we can only understand the 1768 s argument in its hole complexity, it s possible to understand how important this text is to the Form and principles of the sensible world and of the intellectual world dissertation, to the radical development of the kantian thought as a whole and, specially to the critical conception of sensibility.
Keywords: Filosofia - história; Filosofia moderna; Espaço absoluto; Kant, Immanuel, 1724-1804; Absolute space; Substance; CIENCIAS HUMANAS::FILOSOFIA